Cisplatin-Induced Renal Salt Wasting Requiring over 12 Liters of 3% Saline Replacement - Phuong-Chi Pham; Pavani Reddy; Shaker Qaqish; Ashvin Kamath; Johana Rodriguez; David Bolos; Martina Zalom; Phuong-Thu Pham (Case Reports in Nephrology)
Cisplatin is known to induce Fanconi syndrome and renal salt wasting (RSW). RSW typically only requires transient normal saline (NS) support. We report a severe RSW case that required 12 liters of 3% saline. A 57-year-old woman with limited stage small cell cancer was admitted for cisplatin (80 mg/m2) and etoposide (100 mg/m2) therapy. Patient’s serum sodium (SNa) decreased from 138 to 133 and 125 mEq/L within 24 and 48 hours of cisplatin therapy, respectively. A diagnosis of syndrome of inappropriate antidiuretic hormone secretion (SIADH) was initially made. Despite free water restriction, patient’s SNa continued to decrease in association with acute onset of headaches, nausea, and dizziness. Three percent saline (3%S) infusion with rates up to 1400 mL/day was required to correct and maintain SNa at 135 mEq/L. Studies to evaluate Fanconi syndrome revealed hypophosphatemia and glucosuria in the absence of serum hyperglycemia. The natriuresis slowed down by 2.5 weeks, but 3%S support was continued for a total volume of 12 liters over 3.5 weeks. Attempts of questionable benefits to slow down glomerular filtration included the administration of ibuprofen and benazepril. To our knowledge, this is the most severe case of RSW ever reported with cisplatin.